COVID-19 in Princess Marina Hospital, Botswana: An Outbreak Investigation - Siamisang, Keatlaretse; Kebadiretse, Dineo; Smith-Lawrence, Pamela (Interdisciplinary Perspectives on Infectious Diseases, 2022)
The Princess Marina Hospital in Gaborone, Botswana, had an outbreak of COVID-19 from early August 2020. The aim of this paper was to describe the outbreak investigation. The investigation’s specific objectives were to describe the COVID-19 cases in terms of person, place, and time (PPT) and to determine measures to prevent further transmission of the infection. The data reported herein were collected over a 3-month period from beginning of August to end of October 2020. The investigation included all COVID-19 cases i.e. both patients and healthcare workers. It followed the steps of an outbreak investigation. These included assembling an investigation team comprising both the hospital and DHMT staff. All the wards reported their confirmed cases to the infection control team who in turn prepared line lists and case reports. Epicurves were produced from date of positive result. A total of 193 cases were reported, of which 110 (57.0%) were patients and 83 (43.0%) were healthcare workers. The median age was 35 years. Females accounted for 154 (79.8%) participants. Most of the wards were affected. The wards with the highest numbers of cases were female medical ward (39), emergency department (24), gynecology ward (17), and pediatric medical ward (10). Control measures included restricting movement into the hospital as well as clinical screening at all entry points. Furthermore, all patients were tested before admission into the wards. Surveillance of COVID-19 cases was continued beyond the 3 months reported in this paper. COVID-19 can spread rapidly in hospital settings affecting both patients and healthcare workers. Outbreak investigations including describing cases in terms of person, place, and time are critical if the most effective and efficient control measures are to be implemented.